Mikrointervallien akuutit fysiologiset vasteet vastaavat peruskestävyysharjoituksen akuutteja fysiologisia vasteita - Iivari, Mimmi (2024)
Microintervals are very short (< 15 s), high-intensity (~100 % VO2max) intervals, where the work phase is followed by a low-intensity recovery phase (less than 60 seconds). Microintervals can create an alternative form of exercise for low intensity endurance exercise (LIE). The short work periods of microintervals cause small metabolic changes in blood lactate concentration, oxygen consumption and heart rate, and short recovery periods mimics the accumulation of fatigue. These factors enable more high-intensity training compared to continuous high-intensity training. The intensity of the microintervals and the work-rest ratio are used to regulate the acute responses of the exercise, and by manipulating them, the microinterval exercise can be equivalent to the LIE.